Determinant Factors of Entrepreneurial Intention Among Students: A Systematic Literature Review - Ningrum, Linda Agustin; Andayani, Endang Sri; Dwiputri, Inayati Nuraini (Universitas Negeri Malang, 2025)
The study of entrepreneurial intentions has emerged as a significant area of scholarly inquiry, given its fundamental role in driving economic development and fostering innovation across societies. This systematic literature review undertakes a comprehensive examination of the determinant factors influencing entrepreneurial intentions through an analysis of scholarly publications indexed in the Scopus database spanning the period from 2014 to 2024. The research methodology adheres to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) framework, through which 15 articles meeting rigorous inclusion criteria were systematically identified and analyzed. The analysis reveals a complex interplay of factors that shape entrepreneurial intentions, encompassing individual-level variables such as self-efficacy and motivational constructs, educational factors including entrepreneurship curriculum effectiveness, and environmental influences particularly centered on family dynamics and subjective normative pressures. Furthermore, the investigation illuminates distinct patterns in entrepreneurial intention development across secondary and tertiary educational contexts, offering valuable insights into the role of educational systems in cultivating entrepreneurial mindsets. The findings underscore the critical importance of familial support structures and intrinsic motivational drivers in nurturing entrepreneurial aspirations among students. Keywords: Entrepreneurial Intention, Self-Efficacy, Entrepreneurship Education, Family Environment, Motivation